2019
DOI: 10.1007/s12393-019-09205-z
|View full text |Cite
|
Sign up to set email alerts
|

Water Vapor Transport Properties of Polyurethane Films for Packaging of Respiring Foods

Abstract: Thermoplastic polyurethane (PU) polymers with different chemical compositions were synthesized and casted to films, and their water vapor barrier properties at different range of relative humidity (RH) were characterized. The water vapor permeability (WVP) of packaging films is one of their most important properties to identify their suitability for use as packaging materials and is rather a complicated phenomena if the polymer has polar nature. The WVPs of PU films are determined both by permeation measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 34 publications
2
34
1
Order By: Relevance
“…WVP of the packaging films in one of their most significant properties to determine their fitness for use as packaging materials 14 . In addition, WVP is an important property to characterize the overall water-resistance properties of the films 15 .…”
Section: Methodsmentioning
confidence: 99%
“…WVP of the packaging films in one of their most significant properties to determine their fitness for use as packaging materials 14 . In addition, WVP is an important property to characterize the overall water-resistance properties of the films 15 .…”
Section: Methodsmentioning
confidence: 99%
“…Usually, low permeability values are required for packaging films in order to reduce the transfer of moisture from the environment to food and to ensure longer storage times [ 65 ]. However, in case of some types of fresh foods, plastics with high permeability to oxygen and water vapor are required for the packaging to avoid condensation of water vapor inside the packaging, which may lead to microbial growth and food spoilage [ 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the temperature was a significant factor affecting the changes in the meringue moisture content. Turan (2021) revealed that the moisture absorption of the food product through the package is significantly impacted by the rate of water vapor transmission, the thickness of the package, and the environment's relative humidity (RH). At the higher storage temperature, the elevated relative humidity in the environment increased the moisture transmission rate across the packaging material and the food product (Kurek et al, 2014).…”
Section: Moisture Water Activity and Phmentioning
confidence: 99%